Date seed extract-loaded oil-in-water nanoemulsion: Development, characterization, and antioxidant activity as a delivery model for rheumatoid arthritis - Abdul Qadir; Mohd Aqil; Usama Ahmad; Nausheen Khan; Musarrat H Warsi; Juber Akhtar; Muhammad Arif; Abuzer Ali; Satya P Singh (Wolters Kluwer Medknow Publications, 2020)
Rheumatoid arthritis is an inflammatory disorder, affecting around 1% of the world population. Antioxidant activity plays important role to overcome the inflammation associated with arthritis. Phoenix dactylifera (date) seeds, generally considered as a waste product or utilized as food for domestic farm animals, have been used as a source of antioxidants at different disease conditions. The aim of the present study was to enhance the release of date seed extract in order to achieve high antioxidant activity. Nanoemulsion of methanolic extract of date seed was prepared by aqueous titration method. The selected formulations were exposed to thermodynamic stability and dispersibility tests. The optimized nanoemulsions were evaluated on the basis of droplet size (23.14 ± 0.055nm), polydispersity index (0.166 ± 0.124), percent transmittance (99.12 ± 0.0163), refractive index (1.36 ± 0.046), viscosity (cP) (12.30 ± 0.75), conductivity (µS/cm) (347.46 ± 1.10), and drug content (%) (99.67 ± 0.11). The in vitro release studies revealed that final optimized formulation has cumulative release of drug (57.51% ± 2.65%), which was more significantly greater as compared to drug suspension (26.44% ± 1.15%). Further in vitro antioxidant activity studies revealed that the developed methanolic extract of date seed-loaded nanoemulsion has more antioxidant potential when compared with methanolic extract.